Navigating the Digital Revolution in the Food Industry: Consumers’ Perceived Environmental Risks and Purchasing Decisions - Widodo, Arry; Rubiyanti, Nurafni; Madiawati, Putu Nina (Journal of Ecohumanism, 2024)
Online food delivery has transformed the food industry. A new food sector business model has emerged from this revolution of food delivery and consumption. Purchases alter how individuals think online takeaway packaging affects the environment, according to one study. The study focuses on education’s effect on this relationship. Takeout packaging affects brand image, green satisfaction, green trust, and desire to buy eco-friendly food packaging, according to the study. An online survey of Indonesian customers was used to collect data, and the partial least squares structural equation modeling (PLS-SEM) approach was used to analyze it. The results support the model’s claim that green brand image improves repurchase decisions. Consumer pleasure and environmental trust can mediate this effect. All study constructs are reliable and valid. The environmental impact of takeout packaging needs more attention. The national government wants better food packaging rules. The government should ban takeout packaging. Recycling procedures and trash categorization must be developed to streamline recycling. By customizing green marketing to customer understanding, transparency, and education on eco-friendly food packaging boost brand reputation, satisfaction, trust, and risk perception.